Источники надежды в меняющейся действительности (на материале романа Бориса Пастернака Доктор Живаго) - Boginskaya, Anna (Studia Rossica Posnaniensia, 2023)
The article analyzes the sources of hope in the changing reality in Boris Pasternak’s novel Doctor Zhivago. The concept of changing reality is presented through the prism of Zygmunt Bauman’s sociological reflections. In Pasternak’s novel, the high concentration of events of the first part of the 20th century, filled with social upheavals and catastrophes, such as wars and revolutions, becomes part of the protagonist’s biography. The novel reveals the protagonist’s ability to find sources of hope in a hopeless environment. This ability strengths Yuri Zhivago and helps him to live and be engaged in creative activity in hard times. Yuri Andreevich finds salvation in everyday worries, which helps him to overcome chaos in post-revolutionary Moscow. Events filled with the warmth and comfort of everyday life acquire a special status. The next source of hope and inspiration in the book is a creative activity. An inexhaustible source of motivation in the novel is also nature, which is inextricably linked with the theme of creativity. For the protagonist, life is most fully revealed in compassion, active love, admiration for the world, and hope for the triumph of beauty and goodness.